An empire of print the New York publishing trade in the early American republic - Smith, Steven Carl 1981- (The Pennsylvania State University Press, 2017)
"Traces the evolution of New York's publishing trade from the end of the American Revolution to the Age of Jackson. Explores the gradual development of local, regional, and national distribution networks in the early republic"...Provided by publisher
Includes bibliographical references and index
Keywords: Geschichte 1700-1800; Geschichte 1800-1900; Geschichte 1776-1852; Geschichte; Publishers and publishing -- New York (State) -- New York -- History -- 18th century; Publishers and publishing -- New York (State) -- New York -- History -- 19th century; Book industries and trade -- New York (State) -- New York -- History -- 18th century; Book industries and trade -- New York (State) -- New York -- History -- 19th century; Verlag; Buchhandel; New York, NY